Perception of Integrity and Patient Satisfaction Toward the Quality of Service in Government Hospitals: A Study - Andi Surayya Mappangile; Andi Marini Indriani; Dwi Susilowati; Rivaldi Nugraha; Cornelius Prihandoyo; Isradi Zainal (GLOBAL HEALTH SCIENCE GROUP, 2026)
Service quality and the integrity of public service delivery are two fundamental dimensions in building public trust in government hospitals. In the healthcare sector, patient satisfaction is influenced not only by technical aspects of medical services but also by perceptions of transparency, fairness, and the absence of corrupt practices. This study aims to analyze anti-corruption perceptions and patient satisfaction regarding the quality of service at RSUD dr. Kanujoso Djatiwibowo, a government referral hospital in Indonesia. This study employed a cross-sectional design with a quantitative approach. Data were collected using the Anti-Corruption Perception Survey (SPAK), which covers five integrity elements, and the Service Quality Perception Survey (SPKP), which comprises twelve elements of service satisfaction. The sample consisted of 892 service users distributed across 13 hospital service units. The Data was collected through structured questionnaires given directly to patients and their families in 13 hospital service units, analysis was performed descriptively by calculating the Average Value (NRR), the Anti-Corruption Perception Index (IPAK), and the Service Quality Perception Index (IPKP). The results demonstrate that the IPAK score is 99.117 and the IPKP score is 98.319, both of which fall into the